The impact of radioligand therapy on prognosis in patients with lung neuroendocrine tumors - Jóźwik-Plebanek, Katarzyna; Saracyn, Marek; Durma, Adam Daniel; Kołodziej, Maciej; Mądra, Weronika; Dziuk, Mirosław; Janiak, Katarzyna; Balcerska, Zuzanna; Gniadek-Olejniczak, Katarzyna; Kamiński, Grzegorz (Frontiers in Endocrinology, 2026)
BackgroundEvidence on the efficacy and safety of radioligand therapy (RLT) in lung neuroendocrine tumors (LNETs) remains scarce. The limited data available, derived mainly from retrospective analyses are based on small patient cohorts and heterogeneous treatment protocols. The objective of this study was to assess the efficacy and safety of RLT in patients with SSTR–positive LNETs treated with either [¹77Lu]Lu-DOTA-TATE or tandem therapy with [90Y]Y-DOTA-TATE/[¹77Lu]Lu-DOTA-TATE at Polish ENETS Center of Excellence.MethodsWe conducted a retrospective analysis of 22 LNET patients who received RLT and had complete follow-up data. Treatment response and survival outcomes were evaluated. Progression-free survival (PFS) and overall survival (OS) were estimated using the Kaplan–Meier method. Prognostic associations with PFS and OS were explored using univariate and multivariable Cox proportional hazards models, treatment-related AE were graded according to CTCAE.ResultsA total of 22 patients with LNETs (Med. 61 years; 68.2% male) were included. Histology comprised 31.8% typical carcinoid, 54.5% atypical carcinoid, and 13.6% LNET G3. 14 patients received [¹77Lu]Lu-DOTA-TATE and 8 tandem [90Y]Y/[¹77Lu]Lu-DOTA-TATE. At a median follow-up of 54 months, median PFS and OS were 16.0 months (95% CI: 11.2–20.8) and 62.0 months (95% CI: 30.7–93.3), respectively. PFS was longer in patients with high SSTR uptake (34vs16 months; p=0.021) and, in unadjusted exploratory analyses, in those treated with tandem therapy (34vs16 months; p=0.037). OS differed significantly by histology and by prior chemotherapy, while FDG-avid disease was associated with shorter PFS and OS. However, these subgroup comparisons are based on a very small sample and should be regarded as exploratory and interpreted with caution. Treatment was generally well tolerated, with hematologic toxicity being the most common.ConclusionsRLT demonstrated signals of clinically meaningful activity and an acceptable safety profile in patients with advanced LNETs in this small retrospective cohort. Outcomes were numerically more favorable in individuals with high SSTR uptake and in those treated with tandem therapy, but the study was not designed to compare treatment regimens. These exploratory findings should be regarded as hypothesis-generating only and do not provide evidence of comparative efficacy.